A Review of Methods for Detecting Soreness in Horses - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
During the last century and today, the Tennessee walking horse has been used primarily for pleasure and show competition. Unique and natural to the breed is a smooth four-beat "running walk" gait. In the 1950s the accentuated or exaggerated running walk, known as the "big lick" became popular at high-level competitions. The combination of exaggerated high-action step in front and long stride behind is still considered desirable in today's horse show competitions, and it is often achieved through soring. Soring is the practice of applying a substance or mechanical device to the lower limb of a horse that will create enough pain that the horse will exaggerate its gait to relieve the discomfort. In 1970 Congress put into law the Horse Protection Act (HPA) to specifically address the practice of soring by prohibiting the showing, exhibition, or sale of Tennessee walking horses that are found to be sore. Sadly, soring is still being done even after 50 years of HPA enforcement. This report reviews the methods for detecting soreness in horses, in hopes of advancing the goal of ultimately eliminating the act of soring in horses and improving the welfare of Tennessee walking horses. A Review of Methods for Detecting Soreness in Horses examines what is known about the quality and consistency of available methods to identify soreness in horses; identifies potential new and emerging methods, approaches, and technologies for detecting hoof and pastern pain and its causes; and identifies research and technology needs to improve the reliability of methods to detect soreness. This independent study will help ensure that HPA inspection protocols are based on sound scientific principles that can be applied with consistency and objectivity.
Keywords: Agriculture

Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States - National Research Council (The National Academies Press, 2014)
In the United States (U.S.), the Fishery Conservation and Management Act of 1976, now known as the Magnuson-Stevens Fishery Conservation and Management Act (MSFCMA), was the first major legislation to regulate federal fisheries in the U.S. Fishery Conservation Zone (later designated as the U.S. exclusive economic zone). The re-authorization of the MSFCMA passed by Congress in 2006 included additional mandates for conserving and rebuilding fish stocks and strengthening the role of scientific advice in fisheries management. Approximately 20% of the fisheries that have been assessed are considered overfished according to the September 2012 stock status Report to Congress prepared by the U.S. National Oceanic and Atmospheric Administration (NOAA). Overfished refers to a stock that is below the minimum stock size threshold, commonly set to half the stock size at which maximum sustainable yield (MSY) is achieved. Under the provisions of the MSFCMA, rebuilding plans for overfished stocks should take no more than 10 years, except when certain provisions apply. Rebuilding mandates have led to substantial reductions in catch and effort for many fisheries, raising concerns about the consequent social and economic impacts to the fishing communities and industry. Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States reviews the technical specifications that underlie current federally-implemented rebuilding plans, and the outcomes of those plans. According to this report, fisheries management has evolved substantially since 1977 when the U.S. extended its jurisdiction to 8 200 miles, in the direction of being more prescriptive and precautionary in terms of preventing overfishing and rebuilding overfished fisheries. However, the trade-offs between precaution and yield have not been fully evaluated. Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States discusses the methods and criteria used to set target fishing mortality and biomass levels for rebuilding overfished stocks, and to determine the probability that a particular stock will rebuild by a certain date. This report will be of interest to the fishing industry, ecology professionals, and members of Congress as they debate the renewal of the Magnuson-Stevens Fishery Conservation and Management Act.
Keywords: Agriculture

Robust Methods for the Analysis of Images and Videos for Fisheries Stock Assessment: Summary of a Workshop - National Research Council (The National Academies Press, 2015)
The National Marine Fisheries Service (NMFS) is responsible for the stewardship of the nation's living marine resources and their habitat. As part of this charge, NMFS conducts stock assessments of the abundance and composition of fish stocks in several bodies of water. At present, stock assessments rely heavily on human data-gathering and analysis. Automatic means of fish stock assessments are appealing because they offer the potential to improve efficiency and reduce human workload and perhaps develop higher-fidelity measurements. The use of images and video, when accompanies by appropriate statistical analyses of the inferred data, is of increasing importance for estimating the abundance of species and their age distributions. Robust Methods for the Analysis of Images and Videos for Fisheries Stock Assessment is the summary of a workshop convened by the National Research Council Committee on Applied and Theoretical Statistics to discuss analysis techniques for images and videos for fisheries stock assessment. Experts from diverse communities shared perspective about the most efficient path toward improved automation of visual information and discussed both near-term and long-term goals that can be achieved through research and development efforts. This report is a record of the presentations and discussions of this event.
Keywords: Math, Chemistry, and Physics; Agriculture; Surveys and Statistics

An Assessment of Native Seed Needs and the Capacity for Their Supply: Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme weather and wildfires, intensified by climate change, are damaging the native plant communities of landscapes across the United States. Native plant communities are foundational to thriving ecosystems, delivering goods and services that regulate the environment and support life, provide food and shelter for a wide range of native animals, and embody a wealth of genetic information with many beneficial applications. Restoring impaired ecosystems requires a supply of diverse native plant seeds that are well suited to the climates, soils, and other living species of the system. This report examines the needs for native plant restoration and other activities, provides recommendations for improving the reliability, predictability, and performance of the native seed supply, and presents an ambitious agenda for action. An Assessment of Native Seed Needs and the Capacity for Their Supply considers the various challenges facing our natural landscapes and calls for a coordinated public-private effort to scale-up and secure a cost-effective national native seed supply.
Keywords: Agriculture

An Assessment of the Need for Native Seeds and the Capacity for Their Supply: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Across the United States, millions of acres of land have been so disturbed by human activities or severe climate events that significant portions of their native plant communities have been lost and their ecosystems have been seriously compromised. Restoring impaired ecosystems requires a supply of diverse native plant seeds that are well suited to the climates, soils, and other living species of the system. Native seeds are also in demand for applications in urban land management, roadside maintenance, conservation agriculture, and other restorative activities that take into account the connection between native plant communities and the increasingly urgent need for resilient landscapes. Given the varied climatic and environmental niches of the more than 17,000 native plant species of the United States, supplying the desired seed types and species mixes for this wide range of activities is a challenge. As the first phase of a nationwide analysis of the full scope of needs for native plant seeds, this interim report describes the participants in the native plant seed supply chain, makes preliminary observations, and proposes an information-gathering plan for the second phase of the assessment.
Keywords: Agriculture; Surveys and Statistics

A Review of the Citrus Greening Research and Development Efforts Supported by the Citrus Research and Development Foundation: Fighting a Ravaging Disease - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Huanglongbing (HLB) or citrus greening, first observed more than a hundred years ago in Asia, is the most serious disease threat to the citrus-growing industry worldwide due to its complexity, destructiveness, and incalcitrance to management. First detected in Florida in 2005, HLB is now widespread in the state and threatens the survival of the Florida citrus industry despite substantial allocation of research funds by Florida citrus growers and federal and state agencies. As the HLB epidemic raged in 2008, Florida citrus growers began allocating funds for HLB research in hopes of finding short-, medium-, and long-term solutions. This effort created the Citrus Research and Development Foundation (CRDF), an organization with oversight responsibility for HLB research and development efforts in Florida. This report provides an independent review of the portfolio of research projects that have been or continue to be supported by the CRDF. It seeks to identify ways to retool HLB research—which, despite significantly increasing understanding of the factors involved in HLB, has produced no major breakthroughs in controlling the disease—and accelerate the development of durable tools and strategies that could help abate the damage caused by HLB and prevent the possible collapse of the Florida citrus industry.
Keywords: Agriculture

Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia - National Research Council (The National Academies Press, 2009)
Increased agricultural productivity is a major stepping stone on the path out of poverty in sub-Saharan Africa and South Asia, but farmers there face tremendous challenges improving production. Poor soil, inefficient water use, and a lack of access to plant breeding resources, nutritious animal feed, high quality seed, and fuel and electricity-combined with some of the most extreme environmental conditions on Earth-have made yields in crop and animal production far lower in these regions than world averages. Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia identifies sixty emerging technologies with the potential to significantly improve agricultural productivity in sub-Saharan Africa and South Asia. Eighteen technologies are recommended for immediate development or further exploration. Scientists from all backgrounds have an opportunity to become involved in bringing these and other technologies to fruition. The opportunities suggested in this book offer new approaches that can synergize with each other and with many other activities to transform agriculture in sub-Saharan Africa and South Asia.
Keywords: Agriculture

Using Science to Improve the BLM Wild Horse and Burro Program: A Way Forward - National Research Council (The National Academies Press, 2013)
Using Science to Improve the BLM Wild Horse and Burro Program: A Way Forward reviews the science that underpins the Bureau of Land Management's oversight of free-ranging horses and burros on federal public lands in the western United States, concluding that constructive changes could be implemented. The Wild Horse and Burro Program has not used scientifically rigorous methods to estimate the population sizes of horses and burros, to model the effects of management actions on the animals, or to assess the availability and use of forage on rangelands. Evidence suggests that horse populations are growing by 15 to 20 percent each year, a level that is unsustainable for maintaining healthy horse populations as well as healthy ecosystems. Promising fertility-control methods are available to help limit this population growth, however. In addition, science-based methods exist for improving population estimates, predicting the effects of management practices in order to maintain genetically diverse, healthy populations, and estimating the productivity of rangelands. Greater transparency in how science-based methods are used to inform management decisions may help increase public confidence in the Wild Horse and Burro Program.
Keywords: Agriculture

Science and Its Role in the National Marine Fisheries Service - National Research Council (The National Academies Press, 2002)
NMFS has a difficult and complex task in managing U.S. marine fisheries. Despite some successes, too many stocks continue to decline. Over the past decade, several problems have been identified that have contributed to the current dissatisfaction with how marine fisheries are managed. This dissatisfaction is evident from the large number of lawsuits filed by the fishing industry and environmental organizations. One central problem is overfishing. Overfishing issues have been discussed in a series of NRC reports, and these reports identify overcapitalization, and technological and gear improvements as some of the causes. The reports recommend ways to stem these problems and to advance the practice of fishery science at NMFS. This report reiterates some of these recommendations, and makes new recommendations to enhance the use of data and science for fisheries management.
Keywords: Agriculture

The Future Role of Pesticides in US Agriculture - National Research Council (The National Academies Press, 2000)
Although chemical pesticides safeguard crops and improve farm productivity, they are increasingly feared for their potentially dangerous residues and their effects on ecosystems. The Future Role of Pesticides explores the role of chemical pesticides in the decade ahead and identifies the most promising opportunities for increasing the benefits and reducing the risks of pesticide use. The committee recommends R&D, program, and policy initiatives for federal agriculture authorities and other stakeholders in the public and private sectors. This book presents clear overviews of key factors in chemical pesticide use, including: Advances in genetic engineering not only of pest-resistant crops but also of pests themselves. Problems in pesticide use—concerns about the health of agricultural workers, the ability of pests to develop resistance, issues of public perception, and more. Impending shifts in agriculture—globalization of the economy, biological "invasions" of organisms, rising sensitivity toward cross-border environmental issues, and other trends. With a model and working examples, this book offers guidance on how to assess various pest control strategies available to today's agriculturist.
Keywords: Agriculture

Managing Global Genetic Resources: Agricultural Crop Issues and Policies - National Research Council (The National Academies Press, 1993)
This anchor volume to the series Managing Global Genetic Resources examines the structure that underlies efforts to preserve genetic material, including the worldwide network of genetic collections; the role of biotechnology; and a host of issues that surround management and use. Among the topics explored are in situ versus ex situ conservation, management of very large collections of genetic material, problems of quarantine, the controversy over ownership or copyright of genetic material, and more.
Keywords: Agriculture

Improving Fish Stock Assessments - National Research Council (The National Academies Press, 1998)
Ocean harvests have plateaued worldwide and many important commercial stocks have been depleted. This has caused great concern among scientists, fishery managers, the fishing community, and the public. This book evaluates the major models used for estimating the size and structure of marine fish populations (stock assessments) and changes in populations over time. It demonstrates how problems that may occur in fisheries data—for example underreporting or changes in the likelihood that fish can be caught with a given type of gear—can seriously degrade the quality of stock assessments. The volume makes recommendations for means to improve stock assessments and their use in fishery management.
Keywords: Agriculture; Earth Sciences

Review of Northeast Fishery Stock Assessments - National Research Council (The National Academies Press, 1998)
The collapse of cod, flounder, and haddock fish stocks in the Northeast United States has caused widespread concern among managers and fishers in the United States and Canada. The diminishing stocks have forced managers to take strict regulatory measures. Numerous questions have been raised about the adequacy of stock assessment science used to evaluate the status of these stocks and the appropriateness of the management measures taken. Based on these concerns, Congress mandated that a scientific review of the methodology and data used to evaluate these stocks be conducted. In this volume, the committee concludes that although there are improvements to be made in data collection, modeling uncertainty, and communicating between fishers, managers, and scientists, the scientific methods used in the Northeast stock assessments are sound. Recommendations are made on how the stock assessment process can be improved.
Keywords: Agriculture; Earth Sciences

Nutrient Requirements of Swine: Eleventh Revised Edition - National Research Council (The National Academies Press, 2012)
Since 1944, the National Research Council has published 10 editions of the Nutrient Requirements of Swine. This reference has guided nutritionists and other professionals in academia and the swine and feed industries in developing and implementing nutritional and feeding programs for swine. The swine industry has undergone considerable changes since the tenth edition was published in 1998 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eleventh revised edition of the Nutrient Requirements of Swine builds on the previous editions published by the National Research Council. A great deal of new research has been published during the last 15 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of swine in all stages of life, this volume includes information about feed ingredients from the biofuels industry and other new ingredients, requirements for digestible phosphorus and concentrations of it in feed ingredients, a review of the effects of feed additives and feed processing, and strategies to increase nutrient retention and thus reduce fecal and urinary excretions that could contribute to environmental pollution. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Swine represents a comprehensive review of the most recent information available on swine nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious swine production.
Keywords: Agriculture

Livestock - National Research Council (The National Academies Press, 1993)
Agricultural techniques used to increase production of cattle, sheep, and other major species have actually threatened the future genetic diversity of livestock populations, particularly in the Third World. This volume explores the importance of animal genetic diversity and presents a blueprint for national and international efforts to conserve animal genetic resources. It also evaluates genetic techniques useful in conservation programs and provides specific recommendations for establishing data bases and conducting research.
Keywords: Agriculture

Cattle Inspection - Institute of Medicine (The National Academies Press, 1990)
Keywords: Agriculture

Nutritional Energetics of Domestic Animals and Glossary of Energy Terms (The National Academies Press, 1981)
Keywords: Agriculture

Sustainable Agriculture Research and Education in the Field: A Proceedings - National Research Council (The National Academies Press, 1991)
Interest is growing in sustainable agriculture, which involves the use of productive and profitable farming practices that take advantage of natural biological processes to conserve resources, reduce inputs, protect the environment, and enhance public health. Continuing research is helping to demonstrate the ways that many factors—economics, biology, policy, and tradition—interact in sustainable agriculture systems. This book contains the proceedings of a workshop on the findings of a broad range of research projects funded by the U.S. Department of Agriculture. The areas of study, such as integrated pest management, alternative cropping and tillage systems, and comparisons with more conventional approaches, are essential to developing and adopting profitable and sustainable farming systems.
Keywords: Agriculture

Nutrient Requirements of Swine: 10th Revised Edition - National Research Council (The National Academies Press, 1998)
The tenth edition of this essential reference presents new knowledge about the nutritional needs of swine that consider such factors as growth rate, carcass leanness, gender, health, environment, and repartitioning agents. New sections are presented on requirements for amino acids and other nutrients. In addition, an original modeling approach to arriving at energy and amino acid needs for given animals is incorporated in this revision. The book comes with a CD-ROM that allows users to create tables of nutrient requirements for swine of a specific body weight and level of productivity. Nutrient Requirements of Swine covers: Biological concepts that underlie nutrient needs for growth and function. New data on amino acid and energy requirements and the factors that shape them. New findings on lysine and the bioavailability of amino acids. New research results on minerals and vitamins. Nutrient composition of an expanded list of feedstuffs. The role of water in swine physiology, including factors that affect the quality of drinking water. Expanded tables of feed ingredients and their nutrient composition provide bioavailability estimates, fatty acid composition of fats typically used in swine diets, and important information on estimating the amino acid content of crude protein.
Keywords: Agriculture

An Assessment of Atlantic Bluefin Tuna - National Research Council (The National Academies Press, 1994)
This book reviews and evaluates the scientific basis of U.S. management of fisheries for Atlantic bluefin tuna. In particular, it focuses on the issues of stock structure and stock assessments used by the National Oceanic and Atmospheric Administration's National Marine Fisheries Service for management under the International Convention for the conservation of Atlantic Tunas.
Keywords: Agriculture